2001
DOI: 10.1093/chemse/26.4.409
|View full text |Cite
|
Sign up to set email alerts
|

Rating of Different Olfactory Judgements in Alzheimer's Disease

Abstract: Using simple successive tasks we assessed the influence of Alzheimer's disease on the processing of different odours. Fifteen patients with Alzheimer's disease, 15 old control subjects and 15 young control subjects were tested. The experiment included two sessions. Initially 12 odorants were presented, one odorant every minute. For each odour the subjects were asked to rate intensity, pleasantness, familiarity and edibility using linear rating scales. The odorants were then presented a second time and the subj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(30 citation statements)
references
References 55 publications
0
30
0
Order By: Relevance
“…Words, on the other hand, must first have been recognized by their meaning and then judged for edibility. Moreover, patients with Alzheimer's disease in comparison to controls were quite compromised in identification of odors but not in edibility judgments (Royet et al 2001). From this point of view, it may indeed be expected that such presemantic judgment of an odor's edibility would not induce a deeper level of processing than a similarity judgment believed to be based on perceptual qualities.…”
Section: Discussionmentioning
confidence: 97%
“…Words, on the other hand, must first have been recognized by their meaning and then judged for edibility. Moreover, patients with Alzheimer's disease in comparison to controls were quite compromised in identification of odors but not in edibility judgments (Royet et al 2001). From this point of view, it may indeed be expected that such presemantic judgment of an odor's edibility would not induce a deeper level of processing than a similarity judgment believed to be based on perceptual qualities.…”
Section: Discussionmentioning
confidence: 97%
“…It has long been recognized that olfaction is impaired in persons with clinically diagnosed AD 22–27 . Olfactory function is also impaired in MCI, 26–31 a precursor of AD, and in those with at least one copy of the apolipoprotein E ɛ4 allele, 28,32–34 a well established risk factor for AD. In previous research in this cohort, we showed that odor recognition performance predicted incidence of MCI and AD, rate of cognitive decline, and level of AD pathology on postmortem examination 4,5 .…”
Section: Discussionmentioning
confidence: 99%
“…The decline of cued odor identification performance often starts during the fifth (Doty et al, 1984a) and sixth decade of life (Brämerson, Johansson, Ek, Nordin, & Bende, 2004;Wehling, Espeseth, Reivang, Lundervold & Nordin, 2009). Findings are not consistent regarding familiarity: while Royet et al (2001) found that familiarity declined significantly with age, other authors have not confirmed this finding (Gilbert & Murphy, 2004;Larsson & Bäckman, 1997). Further studies of age effects in a sample performing different odor identification tasks are thus called for.…”
Section: Introductionmentioning
confidence: 89%